Facebook as a Digital Public Sphere: Processes of Colonization and Emancipation - Bjarki Valtysson (tripleC: Communication, Capitalism & Critique)
In this article, Facebook, as a communicative space, is treated as a public sphere in order to identify processes of colonization and emancipation. The analysis focuses on Facebook’s communicative-structural contexts, in particular from the viewpoint of user terms, user manoeuvre, privacy/data use policy, and ownership and use of uploaded material. The analysis is also based on qualitative data from Danish Facebook users, where the focus was on the users’ motivation and use, their perceptions of ownership and consumerism, as well as their views on the public/private distinction that Facebook allows for/commands for. Theoretically, the article is grounded in Jürgen Habermas’ various writings on the public sphere, as well as ‘digital adaptations’ to his theory. When looked upon from the communicative-structural contexts, processes of colonization are apparent, particularly in the various grey zones identified in Facebook’s privacy/data use policy, its state-ments of rights and responsibilities and in the fashion in which users are treated as consumers. Even though the Danish Facebook users identified with this, they still conceive of Facebook as being an emancipative communicative space, as they prioritize different features of Facebook, namely networking, practical organisation, maintaining friendships, and leisure.